Exports and Firm Productivity in Turkish Manufacturing: An Olley-Pakes Estimation - Arvas, M. Akif; Uyar, Burak (International Journal of Economics and Financial Issues, 2014)
In this study, we examine the effects of exporting on the industry productivity following a two-step procedure using 4-digits industry level data of Turkish manufacturing sectors for the period 2003-2008. First, robust total factor productivity variable is obtained from a Cobb-Douglas production function following the semiparametric method of Olley and Pakes (1996), since productivity estimation by approximating the weighted sum of the inputs by OLS may suffer from simultaneity and selection biases. In the second stage of empirical analysis, the relationship between productivity and being net-exporter is estimated by fixed-effects panel data method. Results show that, productivity level for net-exporters is lesser than the level for net-importers indicating that industries are more prone to import and more competitive on import markets. We also show that when simultaneity and selection biases are not controlled for, the coefficient for the labor input is biased upward and the coefficient for the capital stock is biased downward. Keywords: Semiparametric estimation; total factor productivity; exports JEL Classifications: C14; D24; L60; O14